COMPARATIVE ANALYSIS OF NATIONAL UNMANNED AERIAL VEHICLE WITH MEASUREMENT OF EFFECTIVENESS METHODS - Maswir, Maswir; Soediantono, Dwi (Journal of Industrial Engineering & Management Research, 2022)
The condition of Indonesia, which consists of many islands, requires effective and efficient defense assets to safeguard sovereignty. With the development of technology, this can be achieved by operating unmanned aircraft. The Agency for the Assessment and Application of Technology (BPPT) has been able to make unmanned vehicle, which are named PUNA SRITI and PUNA MALE. The two BPPT products are defense research projects that are expected to be operated by the TNI in the future. To compare the effectiveness of the two PUNAs in military operations, a measurement of effectiveness (MoE) analysis was carried out.